Blend it like Beckham: Trying to read the ball in the WTO negotiations on industrial tariffs - Santiago Fernandez de Córdoba; Sam Laird; David Vanzetti (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2004)
The current WTO negotiations on industrial tariffs have focused largely on a formula approach to cutting tariffs, but the process of trying to find a compromise that would satisfy all sides has led to a number of propositions that entail blending various elements of formulae, sectoral elimination, exceptions for sensitive products, capping to reduce tariff peaks, provisions for developing and least-developed countries, provisions for recently acceded countries, and extending binding coverage at rates that could be determined in different ways. This blend of approaches is so complex that determing what a country may have to do and what it might expect from others is rather like trying to read one of David Beckham's curved balls. Yet, for many countries the outcome will determine for them whether the Doha Ministerial Declaration of the WTO delivers on its development promises. This paper looks at the various proposals and tries to assess how they measure up against the objectives of the negotiations.
Keywords: 330; WTO negotiations; trade; industrial tariffs; development; special and differential treatment; CGE modelling